Description of Ancient Proverbs (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Proverbs are one of the oldest popular genres of Uzbek folklore, which reflects the worldview, attitude to society and moral norms of the people. This article elucidates certain ancient proverbs and their new versions in today’s literature.